Implementasi Terapi Rohani Kristen Terhadap Penurunan Kecemasan Dan Peningkatan Kualitas Tidur Pasien Pre Operatif Di Rumah Sakit Emanuel Banjarnegara - Erikson Tjeleni, Stevanus; Suandika, Made; Triana, Noor Yunida (Yayasan Inspirasi El Burhani, 2024)
Introduction: Preoperative anxiety is often found in every home and the contributing factor is poor sleep quality. One of the non-pharmacological therapies in overcoming anxiety is spiritual therapy. Christian therapy can help individuals find meaning in their suffering, spiritual therapy can also improve sleep quality. Objective: This activity aims to increase the patient's knowledge that if the patient's sleep pattern is irregular and experiences anxiety, the patient can overcome it with non-pharmacological therapy independently. Method: The method used in this PkM assesses the anxiety scale using HARS and sleep quality using PSQI. Then Christian spiritual therapy is carried out in the form of singing, prayer and pastoral activities. Result: The results of the service showed that the difference in respondents' anxiety before and after the provision of Christian spiritual therapy decreased in the moderate anxiety category by 20%. The mild anxiety category increased by 6.7% and the non-anxious category increased by 13.3%. The results of the service show the results of the quality of sleep of the Community Service respondents before and after the provision of Christian spiritual therapy there is a difference in the number of good sleep quality increases by 66.7% and a decrease in poor sleep quality by 66.7%. Conclusion: Based on the results of the service, it can be concluded that Christian spiritual therapy is very useful in reducing anxiety and improving sleep quality.